A desconstrução do princípio da supremacia do interesse público sobre o privado como resgate dos direitos fundamentais - Baptista, Isabelle de (2010)
The present dissertation aims to realize the desconstruction of the principle of supremacy of public interest over private one, as a way of verifying the violation of fundamental rights and guarantees by Public Administration, when it motivates the administrative act based on the referred principle. So, it will be analyzed the notion of public interest under the States paradigms, for each historical moment reflects various specifical interests of society. Then, it will be presented a study about the principle of supremacy of public interest over private one, based on brazilian and italian theory, as well as the position defended by brazilian authors that suggest the use of ponderation tecnique and not the principle of supremacy of public interest. Then, it will be presented a study about disconstruction refered to Jacques Derrida’s philosophical construction, as a way of revealing the the simulacrous, strategically hidden in the texts submitted to them for analysis. Disconstruction will serve as a philosophical basis for a critical analysis of the brazilian administrative practices and of the principle of supremacy of public interest over private one, to underline the importance of the theory of fundamental rights. These approaches will serve as theorical premises to the analysis of brazilian Superior Court of Justice’s decisions, taken in the year of 2009, concerning to administrative subject, as a way of showing the violation of fundamental rights and guarantees by brazilian Public Administration. The methodology utilized in the was the critical-methodological, based on theory of complexity, once it starts from an approach of the referred principle as a way of showing its contradictions and ambiguities, as well as the occultation of State’s strenght, that subtly imposes practices. Considering that the fundamental rights are, today, in the center of constitutionalism, it is asserted the idea os supremacy os fundamental rights. Desconstruction will serve, here, as a way of rescuing the importance of the effectivation of fundamental rights and guarantees by brazilian Public Administration, as well as the defense of a statal actuation compromised with ethics, alterity and responsability with the future.